Prasangka dan Suudzon: Sebuah Analisa Komparatif Dari Perspektif Psikologi Barat dan Psikologi Islam - Indah Elfariani (Jurnal Psikologi Terapan, 2019)
Individuals are obsessed with knowing the meaning of their behavior. These two concepts have something in common that has negative thoughts to others, feel themselves most righteous, and do not want to listen advice of others. The main difference is that if prejudice is not explained it will damage the individual but in the Islamic concept of suudzon is the first step as a liver disesease that can have a very big impact on self or individual environment. Not infrequently prejudice and suudzon cause enormous conflict for others, even many innocent people experience the resulting impact of unfavorable. Individuals who have already used their minds and bodies to always feel bad about others, change the perception to look more positive in others, make peace with your environment then our lives will always be calm and peaceful.